2014
DOI: 10.1371/journal.pntd.0003055
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Coxiella burnetii in Ruminants on Reunion Island? Prevalence and Risk Factors

Abstract: Q fever is a widespread zoonosis that is caused by Coxiella burnetii (C. burnetii), and ruminants are identified as the main sources of human infections. Some human cases have been described, but very limited information was available about Q fever in ruminants on Reunion Island, a tropical island in the Indian Ocean. A cross-sectional study was undertaken from March 2011 to August 2012 to assess the Q fever prevalence and to identify the major risk factors of C. burnetii infection in ruminants. A total of 516… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 39 publications
2
33
0
2
Order By: Relevance
“…The antigen is a sheep strain (phase 1-2). Sensitivity and specificity of this ELISA test were 87% and 100%, respectively (manufacturer's data) (Cardinale et al 2014). Positive samples were retested.…”
Section: Serum Samples and Serological Examinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The antigen is a sheep strain (phase 1-2). Sensitivity and specificity of this ELISA test were 87% and 100%, respectively (manufacturer's data) (Cardinale et al 2014). Positive samples were retested.…”
Section: Serum Samples and Serological Examinationmentioning
confidence: 99%
“…Q fever is a zoonosis occurring worldwide caused by the Gram-negative bacterium Coxiella burnetii (Rodríguez et al 2010, Cardinale et al 2014. Humans are infected primarily by inhaling an aerosol contaminated with material from the urine or feces of infected animals (Esmaeili et al 2014, Schimmer et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed in other countries on inter-herd transmission of ruminants also showed relevance of transmission via direct contact as well as indirect transmission. Direct transmission was mainly studied by assessing trade data (Nusinovici et al, 2014;Nusinovici, Hoch, Brahim, Joly, & Beaudeau, 2015) and by assessing proxies like proper quarantine procedures (Cardinale, Esnault, Beral, Naze, & Michault, 2014). Indirect transmission was suggested by identified crude risk factors like animal density (Lambton, Smith, Gillard, & Horigan, 2016;Nusinovici et al, 2015Nusinovici et al, , 2014 and spatial clustering (Alvarez et al, 2012;Nogareda et al, 2013).…”
Section: Insights In Source Characterizationmentioning
confidence: 99%
“…The reports have implied that farm animals including cattle, sheep, and goats, play a major role as reservoir of the infection, with high risk to the vulnerable populations including ranchers, veterinarian, butchers and personnel of slaughterhouses [5][6][7]. Transmission routes of the infection to human are including infected ticks, aerosols, direct contact with the infected animal fluids such as milk, urine, seminal fluid, contaminated tissues such as kidneys, mammary glands and lymph nodes [2,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%